2013
DOI: 10.1152/ajplung.00120.2013
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of eotaxin production and eosinophil recruitment by pulmonary autologous macrophage transfer in a cockroach allergen-induced asthma model

Abstract: Beal DR, Stepien DM, Natarajan S, Kim J, Remick DG. Reduction of eotaxin production and eosinophil recruitment by pulmonary autologous macrophage transfer in a cockroach allergen-induced asthma model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
(70 reference statements)
0
3
0
1
Order By: Relevance
“…In addition, eotaxin is the most specific and strongest factor which can affect the function of eosinophil [22]. The finding of an eotaxin decrease compared to the asthma subgroup in blood serum and BALF further showed the efficiency of γT in asthma relief.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, eotaxin is the most specific and strongest factor which can affect the function of eosinophil [22]. The finding of an eotaxin decrease compared to the asthma subgroup in blood serum and BALF further showed the efficiency of γT in asthma relief.…”
Section: Discussionmentioning
confidence: 88%
“…Alternatively, as non-pulmonary macrophages and hematopoietic macrophage precursors have been shown to acquire AM phenotypic features upon exposure to the environment of the lung [74••, 75, 76], transfer of other normal macrophages may suffice. This approach has been employed in murine models of allergic asthma, with conflicting results [77, 78]. A creative variation on this theme is exemplified by the recent report in which macrophages were initially treated ex vivo with prostaglandin E 2 (PGE 2 ) (which exerts a variety of anti-inflammatory or suppressive actions on macrophages, including strongly boosting their IL-10 production) prior to their adoptive transfer into the lungs during HDM challenge.…”
Section: Emerging Therapiesmentioning
confidence: 99%
“…Furthermore, it has been reported that IL-4 deficient mice demonstrated to be spared from asthmatic attack and airway inflammation[ 36 ]. Th2 cytokines, especially IL-4 and IL-13, are crucial mediators of asthma, and both are proved to play an important role in up-regulating the eosinophil chemo-attractants of eotaxin [ 37 ]. There is evidence showing that eosinophilia may be correlated with the induction of AHR and the severity of asthma [ 8 , 38 ].…”
Section: Discussionmentioning
confidence: 99%